(untitled) (Journal of the College of Basic Education, 2025)
Cinema and television are two civilizational interfaces that have a fundamental presence. They have transcended the boundaries of time and place and touched upon all nations and peoples through the moving image, until they have become a tool for disseminating visions and ideas, including raising social and cultural awareness by simulating the various aspects of human life and the concurrent events and situations that concern his life from extensions of the past. And the present and the future because they have access to the largest number of recipients and for different age, social and cultural groups. Among these works is the use of elements of formal language in providing important content that simulates the requirements of society and its individuals through live television programs to create and shape awareness by highlighting various aspects of life, including simulating topics that contribute to strengthening and laying foundations that stimulate societal awareness of women and their educational role through television programs. Direct. As the research aims to study the topic in all its aspects, and from this standpoint, the researcher formulated the research problem with the following question: What are the technical uses and treatments for the expressive work of live television programs and their educational role in empowering women? The importance of the research and the need for it lies in revealing the data and specificity of cinematic discourse through it. In addition to being a resource for students and researchers, it aims to reveal the uses and technical treatments of live television programs and their educational role in empowering women. The researcher adopted the descriptive approach (content analysis) as it is more appropriate for achieving the goals and achieving the desired results